A high-performance flame fuel cell using ethanol as fuels - Wang, K.; Ahn, J.; Shao, Zongping (2009)
A no-chamber solid-oxide fuel cell that operated on a fuelrich ethanol flame was reported. Heat produced from the combustion of ethanol thermally sustained the fuel cell at a temperature range of 500 ~ 830 °C. Considerable amounts of hydrogen and carbon monoxide were also produced during the fuel-rich combustion directly providing the fuels for the fuel cell. The location of the fuel cell with respect to the flame was found to have a significant effect on the fuel cell temperature and performance. The highest power density was achieved when the anode was exposed to the inner flame. By modifying the Ni+Sm0.2Ce0.8O1.9 (SDC) anode with a thin Ru/SDC catalytic layer, the fuel cell envisaged not only an increase of the peak power density to ~ 200 mW/cm2 but also in a significant improvement of the anodic coking resistance. Copyright © 2008 by ASME.